7-Nitroindazole reduces L-DOPA-induced dyskinesias in non-human Parkinsonian primate - M. T. Herrero; J. E. Yuste; L. Cuenca-Bermejo; P. Almela; L. Arenas-Betancur; V. De Pablos; A. Gonzalez-Cuello; E. Del Bel; J. Navarro-Zaragoza; E. Fernández-Villalba (Open Biology, 2023)
Nitric oxide (NO) plays a pivotal role in integrating dopamine transmission in the basal ganglia and has been implicated in the pathogenesis of Parkinson disease (PD). The objective of this study was to ascertain whether the NO synthase inhibitor, 7-nitroindazole (7-NI), is able to reduce L-DOPA-induced dyskinesias (LIDs) in a non-human primate model of PD chronically intoxicated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Six Parkinsonian macaques were treated daily with L-DOPA for 3–4 months until they developed LIDs. Three animals were then co-treated with a single dose of 7-NI administered 45 min before each L-DOPA treatment. Dyskinetic MPTP-treated monkeys showed a significant decrease in LIDs compared with their scores without 7-NI treatment (p < 0.05). The anti-Parkinsonian effect of L-DOPA was similar in all three monkeys with and without 7-NI co-treatment. This improvement was significant with respect to the intensity and duration of LIDs while the beneficial effect of L-DOPA treatment was maintained and could represent a promising therapy to improve the quality of life of PD patients.